Leadership styles and organizational knowledge management activities: A systematic review - Amiri N.A.; Rahim R.E.A.; Ahmed G. (Gadjah Mada University, 2023)
Leaders play a critical role in the success or failure of their organizations. Leaders can be effective in implementing changes, building their organizations capabilities, and improving its performance, or the opposite, they could be ineffective. In this systematic review, the authors aim to summarize the findings of previous quantitative research, published between the period from 2000 to 2018, to identify the effect of various leadership styles on organizational Knowledge management (KM) capabilities and activities. The authors reviewed 50 articles found in well-known databases included Emerald, ScienceDirect, Taylor and Francis, Ebsco, Google Scholar, and others, concerning the impact of leadership when implementing KM in business organiza-tions. The review revealed that transformational, transactional, knowledge-oriented leadership, top executives, and strategic leadership have evidence of their constant and positive effect on the KM process. The authors encourage organizations to use a combination of those styles to max-imize the effect of leadership on KM. The authors also recommend conducting further studies on the effect of the remaining leadership styles, such as the ethical and servant leadership styles on KM and the other specific KM activities. 2020, Gadjah Mada University. All rights reserved.